Development of Digital Marketing for UMKM Udeng Handicrafts: A Community Empowerment Approach through Digital Innovation - Umah, Yuli Choirul; Masrifatin, Yuni; Wawoho, Iwan Sri; Nurmawati, Nurmawati; Jalil, Sulaiman Abdul (STAI Miftahul ULa Nganjuk, 2024)
This community service program aimed to enhance the marketing and economic potential of the Udeng handicraft business in Munung Village, Jatikalen District, Nganjuk Regency. Using the Asset-Based Community Development (ABCD) approach, the project focused on empowering local entrepreneurs by introducing digital marketing strategies, including social media and online shopping platforms. The initiative resulted in increased product sales, with Udeng handicrafts moving from 20 pieces per week to over 40 pieces per week, through both online and offline channels. This paper discusses the methodology, the community's participation, and the significant impact of digital innovation in boosting local businesses.